Screening of ninety herbal products of commercial interest as potential ingredients for phytocosmetics - Mariacaterina Lianza; Manuela Mandrone; Ilaria Chiocchio; Paola Tomasi; Lorenzo Marincich; Ferruccio Poli (Taylor & Francis Group, 2020)
Elastase and tyrosinase are important targets both for cosmetics and for dermatological disorders. In this work, ninety herbal products were tested as inhibitors of these two enzymes. Eleven extracts resulted strongly active. Four out of them (Camellia sinensis, Ginkgo biloba, Rhodiola rosea, Vitis vinifera) inhibited both enzymes, five (Glycyrrhiza glabra, Ribes nigrum, Rheum officinale, Salvia officinalis, Tilia platyphyllos) were active against tyrosinase only, and two (Ceterach officinarum and Cinnamomum zeylanicum) proved selectively active against elastase. The IC50 ranged from 3.1 to 104.9 μg/mL and 19.3 to 164.3 μg/mL, against elastase and tyrosinase, respectively. The most active extracts resulted enriched in flavonoids (from 1.47 to 56.47 mg RE/g of extract) and phenolics (from 37.43 to 123.56 mg GAE/g of extract), indicating also an antioxidant potential. Finally, a positive correlation between enzymatic bioactivities and phenolic content was also established.